Parasitic Protists: Diversity of Adaptations to a Parasitic Lifestyle - Kolářová, Iva; Florent, Isabelle; Valigurová, Andrea (Microorganisms, 2022)
Parasitic protists cause some of the most well-known human and animal diseases such as malaria, toxoplasmosis, amoebic meningitis, sleeping sickness, leishmaniosis, and diarrheal illness of protozoan origin (e [...].